2010
DOI: 10.1590/s1807-59322010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Blood Loss and Transcapillary Refill in Uncontrolled Treated Hemorrhage in Dogs

Abstract: OBJETIVE:This study evaluated retroperitoneal hematomas produced by bilateral injury of iliac arteries (uncontrolled hemorrhage), blood volume loss, transcapillary refill, the effects of volume replacement on retroperitoneal bleeding and the hemodynamic changes with and without treatment.METHODS:Initial blood volume was determined with Tc99m-labelled red cells, and bleeding was evaluated by means of a portable scintillation camera positioned over the abdomen. Previously splenectomized mongrel dogs (16.8 ± 2.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The absence of potential confounding factors that may interfere with coagulation was also verified. No significant decrease in hemoglobin was observed in group H, suggesting the absence of transcapillary refill 40 . As mentioned in the “observation time” section, this compensatory mechanism leads to dilution and could have interfered with ATC.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The absence of potential confounding factors that may interfere with coagulation was also verified. No significant decrease in hemoglobin was observed in group H, suggesting the absence of transcapillary refill 40 . As mentioned in the “observation time” section, this compensatory mechanism leads to dilution and could have interfered with ATC.…”
Section: Resultsmentioning
confidence: 74%
“…Indeed, transcapillary refill begins in the first minutes after hemorrhage. This compensatory mechanism is characterized by the transfer of interstitial fluid to the intravascular area, limiting the consequences of hypovolemia 40 42 . It also leads to dilution and constitutes a potential confounding factor.…”
Section: Methodsmentioning
confidence: 99%
“…Further studies in experimental animals concluded that HSD should be the first resuscitation fluid administered (17) and that doses could be adjusted to sustain animals, even in uncontrolled hemorrhage models (18-20). …”
Section: Introductionmentioning
confidence: 99%
“…Transcapillary refill was evaluated in dogs submitted to uncontrolled hemorrhage by Sallum et al. [ 6 ] I am a co-author of this paper and we found that rebleeding occurred irrespective of whether the condition was treated with isotonic or hypertonic saline. However, as might be expected from some strictly physical considerations, hypertonic saline treatment induced transcapillary refill whereas isotonic saline resuscitation led to capillary extravasation.…”
Section: Resultsmentioning
confidence: 73%